Analysis of web-based GNSS post-processing services for static and kinematic positioning using short data spans - El-Mowafy, Ahmed (Maney Publishing, 2011)
In this paper the use of some of the currently available web-based online engines for the processing of static and kinematic data from a single dual-frequency receiver is evaluated. The study focuses on using these processing services for the determination of the coordinates of temporary control stations from a few hours of observations in the static mode, and in positioning in the kinematic mode, such as in hydrographic mapping, checking as-built utilities and Geographic Information Systems (GIS) data collection. The different services are briefly presented and compared. The static testing was performed using the AUSPOS and CSRS-PPP services. The results show that precision at mm to cm level can be achieved from the former and within a decimetre from the latter. Kinematic testing using the CSRS-PPP service was performed. Its positioning results were compared with independent differential processing of the same data. The impact of varying the data length on the achieved precision is investigated and the resulting positioning error levels are quantified. In general, the precision varies from a few cm to a few decimetres, and it generally improves with longer observation periods. The CSRS-PPP smoothing performance is also evaluated when breaks of satellite visibility take place and compared with the case of good visibility. Some recommendations are given to surveyors interested in using this type of processing service.